Leucocyte numbers and phagocytic activity in turbot Scophthalmus maximus following immunization with Vibrio damsela and Pasteurella piscicida O-antigen bacterins - Santarém, M. M.; Figueras Huerta, Antonio (Diseases of Aquatic Organisms, 1995)
8 pages, 6 figures, 1 table The effects of 2 injected bacterins, Vibrio damsela and Pasteurella piscicida O-antigen bacterins, on the cell type composition of the peripheral blood and head kidney and on the phagocytic activity of the head kidney leucocytes were studied in turbot Scophthalmus maximus L. Blood and head kidney samples were collected from treated and non-treated turbot at different times in the 168 h period after injection. The number of neutrophils increased markedly in the peripheral blood of P. piscicida O-antigen injected turbot 24 h after injection, being significantly higher (p < 0.01) than the neutrophil number in V. damsela O-antigen injected turbot. Forty-eight hours after injection, the numbers of head kidney neutrophils and macrophages in V. damsela and in P. piscicida O-antigen injected turbot increased significantly (p < 0.05) compared with those in saline-injected turbot while the neutrophils in the peripheral blood decreased in fish treated with each of the vaccines. Turbot neutrophils have peroxidase-positive granules and also showed phagocytic capability. The phagocytic rate of the peripheral blood and head kidney phagocytes was higher in turbot injected with bacterins than in the saline-injected turbot, with the maximum phagocytic activity occurring 48 h after injection. Phagocytic activity of phagocytes in peripheral blood, kidney, and spleen was equal. Our data show that the phagocytes of turbot have a low phagocytic affinity for sheep red blood cells in comparison to what has been reported for rainbow trout. Both V. damsela and P. piscicida O-antigen elicited a similar level of a non-specific immune response. M. M. S. thanks the Junta Nacional de Investigaçào Cientifica e Tecnológica (Portugal) for a research fellowship. This work was supported by CICYT grant number MAR91-1133-C02-02 and AGF94-1360-C03-03 from Spain Peer reviewed